Cognitive Behavioural and Melodic Intonation Therapies on Verbal Communication Skills of Persons with Apraxia of Speech - Jacob, Udeme Samuel; Olasoji, Omotolani Edith; Osisanya, Ayo; Pillay, Jace (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
The study investigated the effect of cognitive behavioural therapy (CBT) and melodic intonation therapy (MIT) on the verbal communication skills of persons with apraxia. A pre-test, post-test, and control group quasi-experimental research design was used with a sample of persons with post-stroke apraxia receiving speech and language therapeutic services in Ibadan Metropolis. University College Hospital was selected as the treatment center for the study. Thirty persons with apraxia were purposively selected and assigned to one of three groups: CBT, melodic intonation therapy, or control (N = 30, male = 16, female = 14, mean age = 63.1 years). Twenty-four sessions of CBT and melodic intonation therapy classes were held with the experimental group only. The control group was exposed to placebo treatment over the same period. An apraxia of speech rating scale (ASRS) was administered to assess the verbal communication skills of the prospective participants. Those who met the inclusion criteria were selected for the study. The instruments used were the ASRS, the English proficiency test of oral communication skill rating scale, and two self-developed therapeutic plans. Data were analysed using analyses of covariance and Scheffe’s post-hoc test at a 0.05 level of significance. There was a significant main effect of treatment (CBT and MIT) on the verbal communication skills of the participants (F (2,11) = 200.84, P < 0.05, X = 0.56). Participants in the MIT group had the highest mean score (56.20), followed by those in CBT (37.90), while those in the control group had the lowest mean score (23.80). CBT and MIT were effective in enhancing the verbal communication skills of persons with apraxia. However, MIT showed better outcomes than CBT. Therefore, it is appropriate for speech therapists, pathologists, and other relevant practitioners to adopt these strategies to improve the verbal communication skills of those with apraxia.